A retrospective analysis of all-cause and cause-specific mortality rates in French male professional footballers - Orhant, E.; Carling, C.; Chapellier, J.-F.; Marchand, J.-L.; Pradat, P.-F.; Elbaz, A.; Maniez, S.; Moisan, F.; Rochcongar, P. (Scandinavian Journal of Medicine & Science in Sports, 2022)
This study retrospectively compared all-cause and cause-specific mortality in French male professional football players with data from France's national population. Altogether, 6114 individuals born in Metropolitan France or in one of its overseas territories who played at least one competitive match in France's professional football championships between January 1, 1968 and December 31, 2015, were identified and followed up for vital status obtained from a national reference database until December 31, 2015. Data on all-cause and cause-specific mortality were subsequently compared to the expected number of deaths for the national population after standardization for the year, age, and sex. Ratios between observed and expected deaths provided standardized mortality ratios (SMR) along with 95% confidence intervals (95% CI). Linear trends were investigated using the Poisson trend test. Altogether, 662 player deaths were observed. All-cause mortality overall was lower than that of the national population (SMR: 0.69, 95% CI 0.64-0.75). An excess of deaths from dementia was observed in the players (SMR: 3.38, 95% CI: 2.49-4.50) whereas mortality from diseases of the nervous (SMR: 0.64, 95% CI: 0.35-1.08) and cardiovascular systems (SMR: 0.82, 95% CI: 0.70-0.96), and cancer (SMR: 0.67, 95% CI: 0.58-0.76) was lower. Lower overall mortality and that owing to common cardiovascular and cancer-related diseases were reported in French professional football players compared to France's national population. In line with previous studies, however, excess mortality from dementia was observed in the players. Career length was not associated with all-cause or cause-specific mortality. Prospective matched-cohort studies are necessary to identify the neurologic impact of participation in professional football.